Characteristics of soil physical properties for pond design for aquaculture among rice farmers at Kwabre District - Yeboah, Asare Barfour (2015)
Thesis submitted to Department of Agricultural Engineering, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirements for the degree of Master of Mechanical and Agricultural Engineering, 2009